Innovative Environment Within Organization’s Structure- Case of Oman - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2021)
In today’s age of modernization, the concept of innovation is considered as one of the key factors for organizational growth. At the same time, organizations are expected to adapt culture and environment where innovation can continue to develop. It requires a coordinated efforts by different actors in organization in making sure that the activities and integration process meets the conditions for an effective application. In order to put together the various moving parts of an innovation integration, the organization also needs to evaluate its structure in order to ensure that the activities entailed in the innovation process are not interrupted by organizational bureaucracy. In the case of Oman, the conception of an innovative environment is challenged by a prevailing organizational structure that constitutes hierarchical attributes. The problem with hierarchical structure is that innovation and development are slow. In addition, there is not enough room for creative inputs to be recognized because the decision points rely on the center of authority within the organization. This empirical research highlights the concept of innovative environment within the organizational structures in Oman.